Degradation of Congo Red Dye in Wastewater using Ozonation Method with H2O2 Catalyst - Ria Wulansarie; Muhammad Rozaq; Setijo Bismo; Wara Dyah Pita Rengga (School of Postgraduate Studies, Diponegoro Univer, 2024)
The development of the industrial sector in Indonesia has increased very rapidly, especially in the textile industry. The increasing number of industries has an impact on the amount of industrial waste. Congo red dye is one of the dyes that are often used in the textile industry. Industrial dye waste needs to be processed so as not to damage the environment because the substances contained are harmful to the environment. One way that can be used to neutralize dye waste is ozone. Ozone can be used in many fields such as oxidation of inorganic/organic compounds and disinfection (or control of pathogens). H2O2 catalyst is used to accelerate the ozonation process. In this research the variables used were ozonation time (0.15,30,45,60 minutes), pH conditions (5,7,9) and the concentration of H2O2(0,2.5,5,7.5,10) % mass. Based on the research, it was found that the longer the ozonation time, the higher the pH value, and the more H2O2 used, the better the ozonation process results, namely the lower the concentration of dyes, COD, and BOD5 contained in the wastewater.